1 William Waller Hening, The Statutes at Large: Being a Collection of all the Laws of Virginia 263 (1809) - (:unkn) unknown (My University, 1643)
"Masters of every family shall bring with them to church on Sundays one fixed and serviceable gun with sufficient powder and shott"
Keywords: REQUIRED POSSESSION; CARRY - CERTAIN PUBLIC PLACES; SENSITIVE PLACES